Housing Conditions of the Romanian Population – A Social Problem of High Emergency - Stanciu, Mariana (Calitatea Vieții, 2014)
This paper addresses the housing crisis in Romania in European context, providing an overview and a brief analysis of the most notable trends and concerns. The topic is of crucial importance for the Romanian society and authorities, as Romania clearly stands out in the European Union by the high rate of overcrowding, poor living conditions and lack of access of a large part of the population to decent housing. This alarm signal concludes with a call for social innovation, in order to increase the supply of widely accessible and sustainable housing.